Da leitura-interpretação da proposta à avaliação da argumentação na redação do ENEM: a apropriação da língua (escrita) e o repertório do participante - Parreira, Míriam Silveira (2017)
This thesis proposes to look at argumentation in the ENEM essays, under the perspective of the Émile Benveniste’s Enunciation Theory, as a result of the appropriation of the (written) language and the repertoire mobilized by the participant. Thus, to understand the ENEM reading and writing as speech acts, is to understand them as processes that involve subject-reader / writer-speaker-student and ENEM participant, that appropriates him/herself of the (written) language, instituting him/herself as the “I” before an institutional “you”, in order to, in this inter-subjective relationship, co-construct something about “he”, in a specific time and space. With this, I want to say that this singular, unique manner of the “subject” in organizing the (written) language to the point of making him/herself a subject of the enunciation, and enunciating (him/herself) in the ENEM essay with the purpose of expressing his/her point of view, may occur in the tension of producing the text between that which constitutes itself as the writing rules required in the ENEM competencies, and that which the student manages, or not, to produce as from these demands. Moreover, due to this, it is a work of the use of (written) language in discourse. The corpus analyzed is constituted of proposals of essays from the years 2013 and 2015, ten (10) essays produced at ENEM and the Pedagogic Checking of the ENEM assessment. The analysis shows that all the essays were produced as from the establishment of the figurative framework, in which a dialogue was maintained with the institutional proponent and with the “you’ reader-assessor. In all of them, it was possible to notice the presence of the motivating texts presented in the proposal, which was really expected, for they are a resource on which Subject-reader /writer-speaker-student and ENEM participant bases him/herself on, to develop his/her argumentation. It was not surprising to verify that nearly all the essays maintained their argumentation restricted to the motivational texts, and that the essay with grade one thousand (1,000) showed very little beyond what was in them. In all of them, including the essay of grade one thousand (1,000), the relation with orality is present: ENEM subject-readers/writers-students-participants writes in flows of thought, not distinguishing the oral modality from the written modality, compromising the synthetic processes proper to the (written) language. Apart from this, all the problems found in the essays are related to the appropriation of the (written) language and with the mobilized repertoire, in such a manner that it is possible to conclude that this happens regularly. Thus, the understanding of the essay produced at ENEM as a speech act, after the studies and the analysis carried out in this thesis, it is possible to conclude that it is necessary to discuss the way of teaching writing in the schools. Writing must be treated, thus, as a process that implies planning and management of and over the (written) language, requiring necessarily, an elaboration work that should be carried out throughout Basic Education. In this manner, it will be possible to foster in the students the constitution of themselves as capable subject-reader/writer-speakers, among other things, so they can attend to the demands of assessments such as that of ENEM. Thus, for the students, it would be in the flow of their competencies in written production to write a dissertation-argumentation text, as their relation with the (written) language would be that of the experiencing of a process with the Portuguese Language all through their school life.